2007
DOI: 10.2224/sbp.2007.35.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Stress, Burnout and Job Satisfaction in Turkish Midwives

Abstract: This descriptive and cross-sectional study was conducted to determine the levels of work-related stress, burnout and job satisfaction in midwives. It was conducted between March 1 and April 31, 2005, in 35 public health clinics which provide primary health care in the city of Antalya. The research population consisted of 325 midwives who responded to a questionnaire about the sociodemographic characteristics of the subjects and their working places as well as the Work-Related Strain Inventory (Revicki, May, &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 9 publications
3
22
1
3
Order By: Relevance
“…However, studies in Turkish midwives (Bodur , Oncel et al . ) did not find a significant relationship between the length of employment and job satisfaction. Moreover, a study of Estonian midwives found no significant association between job satisfaction and age, ethnicity, work abroad or increased responsibility (Lazarus et al .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, studies in Turkish midwives (Bodur , Oncel et al . ) did not find a significant relationship between the length of employment and job satisfaction. Moreover, a study of Estonian midwives found no significant association between job satisfaction and age, ethnicity, work abroad or increased responsibility (Lazarus et al .…”
Section: Discussionmentioning
confidence: 73%
“…In the NEXT study (Stordeur et al 2003) a curvilinear relationship between job satisfaction, age and seniority was found; the scores were higher in the lowest and highest age groups and in the years of seniority and lower after up to 5 years of experience from graduation. However, studies in Turkish midwives (Bodur 2002, Oncel et al 2007) did not find a significant relationship between the length of employment and job satisfaction. Moreover, a study of Estonian midwives found no significant association between job satisfaction and age, ethnicity, work abroad or increased responsibility (Lazarus et al 2005).…”
Section: Discussionmentioning
confidence: 94%
“…This study adopted a descriptive survey design, commonly employed in previous research on this topic [25,38,44,45] . Descriptive research is useful in a study that aims to identify individuals' emotional or psychological responses to a set situation [46] .…”
Section: Designmentioning
confidence: 99%
“…It has been found by previous researchers that an increase in the length of time working as a nurse resulted in lower levels of Emotional Exhaustion [61] and Depersonalisation [44] . It has been suggested that nurses with more work experience report less burnout because of their high professional title, experience, self-control and a well-rounded psychological coping mechanism [20] .…”
Section: Discmentioning
confidence: 99%
“…Many studies have indicated that workers in the health sector are the group most exposed to WPS (Michie, 2002;Rossi, Perrewé , & Sauter, 2006;Hackett, Palmer, & Farrants, 2009;Fiabane, Giorgi, Sguazzin, & Argentero, 2013). WPS is considered a major cause of negative effects on institutions (Brown, 2012), including physical and psychological illness, high turnover and absenteeism (Wright, 2014), family conflict (Oncel, Ozer, & Efe, 2007), violence (Saleh & Saif, 2014), and decline of career commitment (CC) London, 2014).…”
Section: Introductionmentioning
confidence: 99%